Implementasi Nilai-nilai Karakter Bangsa pada Konten Bermain Bahasa Anak di TK Negeri 01 Pajo - Rostianingsih Rostianingsih; Muslim Muslim; Syahru Ramadhan (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2025)
This study aims to determine the implementation of national character values in language play content in children at State Kindergarten 01 Pajo. The background of the problem is the importance of character education from an early age in shaping children's attitudes that reflect the noble values of the Indonesian nation. Language learning that involves games can be an effective means to instill these values while improving children's language skills. This research uses a qualitative approach with a case study method to deeply understand how character values are applied in language play activities. The data collection techniques used were observation, interview, and documentation. The data sources in this study include teachers, children, and documentation of learning activities at TK Negeri 01 Pajo. The data analysis technique was carried out with an inductive approach where the collected data was analyzed systematically to draw conclusions regarding the application of character values in language play activities. The results showed that in State Kindergarten 01 Pajo the implementation of national character values such as patriotism, mutual cooperation, unity, honesty, and responsibility are strongly instilled through language play activities. Children are actively involved in various games such as playing Mbojo language, rhymes, rhymes, drama, imaginative conversations as well as word games and city vocabulary. The activities not only develop language skills, but also help children understand and apply the values of national character in their daily lives.